Split Cyclin-Dependent Kinase 4/6–Retinoblastoma 1 Axis in Pancreatic Cancer - Huang, Xing; Zhang, Gang (Frontiers in Cell and Developmental Biology, 2020)
Drugs targeting the CDK4/6-RB1 axis have shown efficacy against multiple solid cancers, but their therapeutic potential in pancreatic cancer remains poorly defined. A recent report proposed that a “tailored” combination of first-line and second-line CDK4-targeting drugs would hold promise for pancreatic cancer treatment. Indeed, this therapeutic strategy exhibited significantly suppressive effects on pancreatic cancer patient-derived cell lines and tumor tissue in vitro. However, the study neglected immune involvement and the influence of CDK6 and RB1 in CDK4 inhibition-based treatment. Herein, we reveal multiple new facets of the CDK4/6-RB1 axis in pancreatic cancer, highlighting the complexity of this signaling axis for future prognostic and therapeutic targeting.